2018
DOI: 10.1097/jte.0000000000000040
|View full text |Cite
|
Sign up to set email alerts
|

Experiential Learning Enhances Physical Therapist Student Confidence in Management of Neurologically Involved Adults and Children

Abstract: Introduction. Clinical experiences are an integral part of professional physical therapist (PT) education programs. Hands-on engagement helps foster the critical thinking skills necessary to successfully navigate the complexity of clinical practice during a PT student's final clinical internships. As PT students advance through an entry-level professional program, their clinical decision-making skills improve; however, they lack self-confidence in working with both adult and pediatric patients pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(25 citation statements)
references
References 21 publications
2
22
0
1
Order By: Relevance
“…e results of this study, in agreement with previously published research, provide favorable data to support the inclusion of EL in DPT curricula to improve students' perceptions of their clinical reasoning and self-efficacy. [4][5][6][7][8][9]21 Our findings are consistent with previous research that identified EL as an educational approach that resulted in increases in clinical reasoning of allied health students. 8,9,21 e significant difference in the change scores for the SACRR between dose groups suggests that a higher dosage of pediatric EL during the DPT curriculum could have a greater impact on students' development of clinical reasoning.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…e results of this study, in agreement with previously published research, provide favorable data to support the inclusion of EL in DPT curricula to improve students' perceptions of their clinical reasoning and self-efficacy. [4][5][6][7][8][9]21 Our findings are consistent with previous research that identified EL as an educational approach that resulted in increases in clinical reasoning of allied health students. 8,9,21 e significant difference in the change scores for the SACRR between dose groups suggests that a higher dosage of pediatric EL during the DPT curriculum could have a greater impact on students' development of clinical reasoning.…”
Section: Discussionsupporting
confidence: 89%
“…Our findings are consistent with previous research that identified EL as an educational approach that resulted in increases in clinical reasoning of allied health students. 8,9,21 The significant difference in the change scores for the SACRR between dose groups suggests that a higher dosage of pediatric EL during the DPT curriculum could have a greater impact on students’ development of clinical reasoning. One potentially valuable element that was not available to the low EL group in the current study was the experiential feedback from the clinic therapist and the patient provided to the high EL groups when they returned to the clinic the following week to implement the planned treatment ideas and discuss goals.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Se observa que en la investigación de Dewi se utilizó una sola sesión y mostró eficacia parcial, y la de Marshall,4 sesiones y mostró eficacia. Al revisar la literatura relacionada, se encuentra que cuatro sesiones de educación experiencial han mostrado ser eficaces para generar cambios en variables psicológicas, por ejemplo: (Siami-Namin, Flores, Tavakoli, Siami-Namin, & Jones, 2021;Bianco, y otros, 2019;Peterson-Ahmad, 2018;Alvarez & Jobst-Hendrik, 2018;Barta, Flores, & Edwards, 2018).…”
Section: Antecedentes Investigativos De Ee Para Prunclassified